Senescence in natural populations of animals: Widespread evidence and its implications for bio-gerontology - Nussey, Daniel H. (Ageing Res Rev, 2012)
That senescence is rarely, if ever, observed in natural populations is an oft-quoted fallacy within bio-gerontology. We identify the roots of this fallacy in the otherwise seminal works of Medawar and Comfort, and explain that under antagonistic pleiotropy or disposable soma explanations for the evolution of senescence there is no reason why senescence cannot evolve to be manifest within the life expectancies of wild organisms. The recent emergence of long-term field studies presents irrefutable evidence that senescence is commonly detected in nature. We found such evidence in 175 different animal species from 340 separate studies. Although the bulk of this evidence comes from birds and mammals, we also found evidence for senescence in other vertebrates and insects. We describe how high-quality longitudinal field data allow us to test evolutionary explanations for differences in senescence between the sexes and among traits and individuals. Recent studies indicate that genes, prior environment and investment in growth and reproduction influence aging rates in the wild. We argue that – with the fallacy that wild animals do not senesce finally dead and buried – collaborations between bio-gerontologists and field biologists can begin to test the ecological generality of purportedly ‘public’ mechanisms regulating aging in laboratory models.